The Usefulness Concept Of Social Arithmetics For Social Sciences Learning Outcomes - Andy Ahmad; Otto Fajarianto (International Journal of Education, Information Technology, and Others, 2020)
Social arithmetic is used in solving everyday problems such as profit and loss, interest rates, discounted prices and tax calculations and others. Students also learn PPh material contained in social sciences subjects, students are expected to be able to understand the concept of social arithmetic. Do students who have a good understanding of the concept of social arithmetic can solve problems regarding PPh to the maximum. The study was conducted at Bekasi's Citra Mandala Middle School. The method that used in this study is a quantitative descriptive method with survey techniques through the correlation approach. Based on the calculation of the correlation index numbers of variables X and Y, the correlation index obtained = 0.90. rxy or r count is consulted with rtable with a significance level of 0.05 with the number of respondents 30 (n = 30) is 0.361, then r count is greater than rtable that is 0.90> 0.361 therefore Ho is rejected and Hi accepted. In other words the application of the mastery of the concept of social arithmetic to social sciences subjects gives positive results. The conclusion from the results of the study is that there is a significant positive relationship between the mastery of the concept of social arithmetic to social sciences learning outcomes.